PENERAPAN MODEL PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA KELAS 5 SD - Widiantono, Nugroho (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
ABSTRACTÂ Based on the observation of science learning activities especially KD 7.3, at the fifth grade students of SDN Lanjan 02 turns out the achievement score of teacher and student activity is low. Similarly, the results of learning. This study aims to improve the activity and learning outcomes of science through the implementation of interactive learning model in fifth grade students of SDN Lanjan 02 second semester in the academic year of 2015/2016. This type of research is a collaborative type class room action research conducted in two cycles that each cycle consists of three meetings. The instruments of the data collection are used test and observation. Technique of data analysis using comparative descriptive method by comparing learning activity, learning result and mastery learn from before action, with condition after done action covering cycle I and cycle II. Based on the observation results obtained percentage of average score of individual student activity increased by 24.40% from pre cycles who get percentage 60.71%. The average percentage of student group activity score increased from pre-group with no group activity, increased to 59.50% in cycle I and increased to 81.25% in cycle II. Learning outcomes experienced an average grade increase of 17.39 points from the average pre cyclesÂ class of 67.61. This means that the application of interactive learning model can improve student activity and learning outcomes in science learning.